Association analysis of PPARGC1A mutations with meat quality parameters in a commercial hybrid pig population - T. Erkens; S. De Smet; K. Van den Maagdenberg; A. Stinckens; N. Buys; A. Van Zeveren; L.J. Peelman (Czech Journal of Animal Science, 2010)
Peroxisome proliferator-activated receptor γ coactivator 1α (PPARGC1A) is a promising candidate gene for selection on meat and carcass quality traits in the pig industry. In the pig, several SNPs have been reported in both coding and regulatory regions of this gene, some of which were associated with fat characteristics, but none of these associations have been confirmed and many SNPs have not yet been evaluated. Therefore, 18 PPARGC1A SNPs were genotyped in 65 slaughter pigs of a commercial hybrid population and used in an association analysis with multiple muscle and carcass traits. Several SNPs located in the 3'UTR and exon 8 and 9 of PPARGC1A were significantly (P < 0.05-0.001) associated with various carcass composition, tenderness and muscle fibre traits. They could potentially serve as DNA selection markers, if their impact was to be confirmed by a functional analysis.